Primary religious socialization agents and young adults' understanding of religion: connections and disconnections. Issue 2 (3rd April 2019) - Golo, Ben-Willie Kwaku; Broo, Måns; Sztajer, Sławomir; Benyah, Francis; Ray, Sohini; Sarkar, Mallarika
ABSTRACT: A recurrent critique towards socialization theory is its emphasis on stability and disregard for change. Some case studies in the YARG project, particularly that of Ghana, do indeed point to the central role and influence that young adults ascribe to their primary socialization agents. In these contexts, personal religiosity is described as being in accordance with the values of parents and family, making religious transmission from one generation to another appear like a seamless affair. However, data from these contexts also point to how secondary socialization agents, such as peers, media and secular education, play a central role for how young adults maintain their personal religiosity. The aim of this paper is to analyze how young adults in Ghana, India and Poland describe the role of primary socialization agents on their religiosity, but also, to critically discern this influence as against that of secondary socialization agents. This article builds on both survey and interview data.